Understanding Relationship Green Entrepreneurship And Circular Economy - Kartika Nuringsih; Nuryasman MN (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
Align with the economy developing progress. The study investigates the relationship among some constructs, namely green entrepreneurship education (GEE). Environmental citizenship behaviour (ECB). Green entrepreneurial intention (GEI). And perceived circular economy (PCE). These relationships involve some direct and mediating effects among constructs in understanding the circular economy. It involves 123 students from some business management schools and economic faculty in Jakarta. Smart-PLS is a tool for running data with the following results: GEE influences ECB with a contribution of 26.38 per cent. ECB contributes 40.45 per cent while GEE supports 11.25 per cent toward GEI. In this case. ECB mediates the relation between green entrepreneurship education and green entrepreneurship intention. When associated with the circular economy. The role of GEI mediates ECB to PCE. However. ECB only impacts 6 per cent. Meanwhile, GEI is 32.72 per cent in forming students’ perception of the circular economy. It shows the ECB has not been able to develop an understanding of the circular economy. Hence. It needs a literacy of circular economy as a mechanism to enrich knowledge in entrepreneurship education programs.